Speaking Anxiety in Virtual Classroom Presentations: How Did Secondary School Students Experience It? - Permatasari, Dita; Mobit, Mobit (Journal of Teaching of English, 2021)
In this era, speaking is very important for all sectors, particularly in the field of education. But, most students tend to be reluctant to speak in English due to several factors. One of them, they have anxieties which enable them burdened to speak in the target language. Therefore, this research aims to investigate students experiences on speaking anxiety in virtual classroom presentation and to figure out the way to manage it. The researcher used qualitative research and used narrative inquiry as the research design. The data collected through semi-structured interview. Two participants from Senior High School students in Bekasi are required to fully participate in the interview. The result of this research showed that the students have afraid feelings to speak English, the students are blank while it starting in speaking, question and answer session is the biggest challenge for student in virtual classroom presentation and supporting to keep in the virtual classroom presentation is important suggestion to students who feel anxiety, and also the students reduce the anxiety with practice.